2021
DOI: 10.29374/2527-2179.bjvm106020
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting of 3D anatomical models of flat and long thoracic limb bones of domestic cats (Felis catus Linnaeus, 1758)

Abstract: Bioimpressão de modelos anatômicos 3D de ossos planos e longos do membro torácicos de Gatos Domésticos (Felis catus Linnaeus, 1758

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
2
Order By: Relevance
“…Haroglu et al (2022), in a study of the effectiveness of 3D printed sheep brain models compared to cadaveric materials, found that 3D printed models can be considered as a supplement teaching resource to cadaveric materials in veterinary anatomy education, particularly when students are supposed to learn more in a limited time. Elias’ et al (2021) printed 3D anatomical pieces which are true to the real parts of the flat (scapula) and long (humerus, radius and ulna) bones of the thoracic limb in cats. The obtained 3D models were similar to the real bones and included the anatomical particularities of the species, which can be used interactively and dynamically to teach comparative and applied anatomy.…”
Section: Use Of 3d Printing In Veterinary and Animal Sciencesmentioning
confidence: 99%
“…Haroglu et al (2022), in a study of the effectiveness of 3D printed sheep brain models compared to cadaveric materials, found that 3D printed models can be considered as a supplement teaching resource to cadaveric materials in veterinary anatomy education, particularly when students are supposed to learn more in a limited time. Elias’ et al (2021) printed 3D anatomical pieces which are true to the real parts of the flat (scapula) and long (humerus, radius and ulna) bones of the thoracic limb in cats. The obtained 3D models were similar to the real bones and included the anatomical particularities of the species, which can be used interactively and dynamically to teach comparative and applied anatomy.…”
Section: Use Of 3d Printing In Veterinary and Animal Sciencesmentioning
confidence: 99%
“…The bony specimens were digitalized and scanned using the EINSCAN PRO 2X MULTI-FUNCTIONAL HANDHELD 3D SCANNER (SHINING 3D) (SHINING 3D Tech Co., Ltd. Hangzhou, China) (29,47,53,54). The average scanning time was approximately 30 minutes (47,53).…”
Section: Animalsmentioning
confidence: 99%
“…The bony specimens were digitalized and scanned using the EINSCAN PRO 2X MULTI-FUNCTIONAL HANDHELD 3D SCANNER (SHINING 3D) (SHINING 3D Tech Co., Ltd. Hangzhou, China) (29,47,53,54). The average scanning time was approximately 30 minutes (47,53). The images taken by the 3D scanner were handled and processed by a software program called Prusa Slicer 2.5.2 (PRUSA RESEARCH by JOSEF PRUSA, Czech).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Com a finalidade de exibir a morfologia, foram digitalizados e impressos, e as estruturas anatômicas principais foram mantidos para estudos comparativos das espécies de interesse veterinário (REIS et al, 2017). Elias et al (2021) afirmam que o uso de técnicas como a impressão 3D auxilia no aprendizado dos estudantes, uma vez que é criada a conexão entre a anatomia conceitual e aplicada, assim, aprendendo de forma interativa, cooperativa e dinâmica, a aquisição de conhecimento se dá no âmbito auditivo, visual, sinestésico e nas suas inter-relações; em um curso de medicina veterinária, por exemplo, pode-se dar a falta para algum modelo biológico natural,já com a remodelagem em 3D é possível suprir essa necessidade, permitindo com que os alunos tenham acesso a peças similares as reais.…”
Section: Introductionunclassified